RGB+D*(t) or the Spatial Manifold Image on Designing Virtual Spaces through Collective Live Volumetric Video Streaming (Architecture Image Studies, 2025)
The article explores the evolution of social spaces from physical to digital realms, examining the role of Spatial Montage in creating immersive digital environments in Game Engines through live 3D scanning and streaming. By analysing the transition from traditional ‘third places’ to contemporary ‘fourth places,’ we discuss how social media platforms facilitate new forms of community making and social interactions, including the spatial screen dimension and transforming the home into a vibrant hub for online gatherings. Reflecting on a project that explores online streaming culture and the role of moving images in architectural design, we combine theoretical insights with the making of and applications in our project called ‘Be My Guest!’ to re-examine the concept of spatial montage as a method for digital placemaking. This approach integrates live volumetric 3D scans into physical spaces using spatial computing and streaming technologies, prompting a discussion on how this could transform architectural environments and influence how we approach architectural design in Web 2.0.Author Biographies Cenk Güzelis, Cenk Güzelis, ./studio3, Department of Experimental Architecture, University of InnsbruckCenk Güzelis is an architect, creative technologist, and new media artist. He researches and educates at the intersection of architecture and XR, exploring expanded spatiality at the ./studio3, Department of Experimental Architecture at the University of Innsbruck. He is a board member of the CSC Immersive Arts, A Centre for The Expanded Moving Image – the Immersive Arts Department of the National Film School of Italy.Anna Pompermaier, Anna Pompermaier ./studio3, Department of Experimental Architecture, University of InnsbruckAnna Pompermaier is an architect, researcher, educator, and media artist based in Innsbruck, Austria, where she is a faculty member and PhD candidate at ./studio3, Department of Experimental Architecture at the University of Innsbruck. Her research explores immersion at the intersection of spatial design, new media technologies, and real-world 1:1 applications in architecture.Me AndOther Mewww.meandother.meCenk and Anna co-founded the new media-driven artistic and architectural research studio named Me AndOther Me, where they explore the future of our spatial experiences and communication through practical applications of social mixed reality experiences focused on online culture, post- human critique, and the spatial web. They investigate how social media and the internet have reshaped spatial experiences, leading to networked virtual spaces as alternative sites for social and cultural engagement. Their artistic and architectural research has been presented at several conferences, including ACADIA (USA), strand (RS), LMDA (LV), and highlighted in diverse publications, such as for R.I.B.A., SOBRE (ES), and MOUSSE (IT) among others. Their works and collaborative projects have been exhibited at Ars Electronica Festival (AT), L.E.V. (ES), IDFA (NL) and Laval Virtual (FR), Impakt (NL), iMAL (BE), Daejeon Museum of Art (South Korea) and more. They have delivered keynotes at various events, including DOKLeipzig (DE) and The Future of Living Conference at Bozar in Brussels (BE).